Оптимальное управление распределением материальных потоков технологической линии производства газобетона - Кулинич, Э. М. (НТУ "ХПИ", 2014)
Предложено повышение эффективности технологической линии приготовления газобетона путем решения задачи оптимального распределения ресурсов с целевой функцией в виде позинома. Обосновано решение этой задачи методами геометрического программирования. Оптимальное управление синтезируется как распределение ресурса энергии по ее технологическим аппаратам.

There is offered an improvement of the effectiveness of control of aircrete production technological line by means of solution to a problem of optimal allocation of resources with an objective function in the form of pozinom. Optimal control is synthesized as distribution of an energy resource to its technological devises. The solution to this task by geometric programming methods was proved. Optimal control is synthesized as the distribution of energy resource to its technological devices. When using pozinomial integrand in the optimal control of aircrete preparation task, the method of Pontryagin can be used, by this a maximum of Hamilton function is determined by taking into account the maximum value of the integrand, which can be easily found by help of geometric programming.
Optimal control by distribution of material flows of aircrete production technological line
Keywords: геометрическое программирование; позином; газобетон; optimal control; technological line; geometrical programming; technological process; pozinom; aircrete; material flows